Effect of serum uric acid level on maternal and neonatal outcome in patients with hypertensive disorders of pregnancy at HSK Hospital, Bagalkot: A prospective and observational study - Neel Prajapati,; Sujay Heranjal,; Varsha Chakrakodi Raghuram,; Santosh Rathod ,; Ashalata Mallapur, (Asian Journal of Medical Sciences, 2022)
Background: Uric acid, a metabolite of purine metabolism, is considered as a marker of hypertensive disorder of pregnancy (HDP) severity. An increase in serum uric acid level in pregnant mothers has been found to be associated with the disease severity. Aims and Objectives: The present study intended to evaluate the effect of serum uric acid level in maternal and neonatal outcome in cases of hypertensive disorders of pregnancy. Materials and Methods: This prospective and observational study was conducted on patients with HDP from December 2017 to April 2019. The study was conducted on 274 subjects who visited the Department of Obstetrics and Gynecology, HSK Hospital, Bagalkot. The participants were categorized into two groups according to their serum uric acid level (<6 mg/dL and ≥6 mg/dL). Serum uric acid was estimated by enzymatic colorimetric method. Maternal and neonatal outcomes were recorded. Follow-up was done till the discharge of the mother and child from the hospital. Data were analyzed using coGuide software. Results: The majority of the participants were in the age group of 18–23 year (52.91%). No significant association was observed between serum uric acid groups and maternal parameters such asparity, gestational age, onset of labor, mode of delivery, and maternal complications (P>0.05). There was statistically no significant difference between serum uric acid groups in neonatal outcomes such as Apgar score 1 min and 5 min, IGUR, NICU admission, and reason for NICU admission (P>0.05) except for still birth. Still birth was found to be more in patients with serum uric acid ≥6mg/dl (19.64%) group compared to <6 mg/dl (8.64%) with P=0.008. Conclusion: This study shows that there was no significant association between adverse maternal and neonatal outcomes with increased level of serum uric acid.